2022
DOI: 10.1101/2022.06.27.22276790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BNT162b2 effectiveness against Delta & Omicron variants in teens by dosing interval and duration

Abstract: Background and Objectives Two- and three-dose BNT162b2 (Pfizer-BioNTech) mRNA vaccine effectiveness (VE) against SARS-CoV-2 infection, including Delta and Omicron variants, was assessed among adolescents in two Canadian provinces where first and second doses were spaced longer than the manufacturer-specified 3-week interval. Methods Test-negative design estimated VE against laboratory-confirmed SARS-CoV-2 infection among adolescents 12-17 years old in Quebec and British Columbia, Canada between September 5, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The inconsistency in methodology, especially the definition of COVID-19 vaccine breakthrough infections among different studies limits the comparison of findings. Nonetheless, several studies demonstrated that the two-dose BNT162b2 vaccine provides strong protection against SARS-CoV-2 delta variant in adolescents (40,45,46). However, as more transmissible novel strain, omicron variant became prevalent worldwide since the start of 2022, the vaccine effectiveness was found to be decreased remarkably (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inconsistency in methodology, especially the definition of COVID-19 vaccine breakthrough infections among different studies limits the comparison of findings. Nonetheless, several studies demonstrated that the two-dose BNT162b2 vaccine provides strong protection against SARS-CoV-2 delta variant in adolescents (40,45,46). However, as more transmissible novel strain, omicron variant became prevalent worldwide since the start of 2022, the vaccine effectiveness was found to be decreased remarkably (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, several studies demonstrated that the two-dose BNT162b2 vaccine provides strong protection against SARS-CoV-2 delta variant in adolescents (40,45,46). However, as more transmissible novel strain, omicron variant became prevalent worldwide since the start of 2022, the vaccine effectiveness was found to be decreased remarkably (46)(47)(48). In this research, the 6-month postvaccination follow-up period through which the cases with breakthrough infections were diagnosed coincided with the time span when the omicron variant displaced the previously dominant delta variant in Turkey (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Since the start of the pandemic, strategies such as vaccination or therapeutic interventions using monoclonal antibodies or antivirals have been used to prevent and control the infection [ 1 ]. Amongst them, vaccination remains the only preventative measure and has been proven effective against SARS-CoV-2 infection from earlier variants [ 2 , 3 , 4 ] and remains effective at protecting from severe outcomes caused by newly emerged variants of concern (VOCs) [ 5 , 6 , 7 ]. Currently approved vaccines target predominantly the Spike glycoprotein (S), which is responsible for viral entry.…”
Section: Introductionmentioning
confidence: 99%